Simulation Analysis of Dynamic Contact of Gear System based on Dynamic Relaxation Method - Zhang Wei; Xiao Zhengming; Wu Xing; Liu Xiaoqin; Cheng Yanli (Jixie chuandong)
Aiming at the problem of system threshold of high- frequency oscillation often appear on gear system starting in the light load gear dynamic analysis simulation system,an method of eliminating the system oscillation caused by initial loading based on the dynamic relaxation is presented. Firstly,the gear system preloading dynamic relaxation process is analyzed. Furthermore,the key technology of dynamic relaxation method in the gear system dynamic simulation based on LS- DYNA platform is put forward. Finally,the effectiveness and better convergence of method for using in the in gear system dynamic simulation analysis are verified by comparing with the simulation results of traditional way of loading.